Роль міжнародних судових установ у формуванні та реалізації звичаєвого міжнародного права - Андрейків, Андрій Іванович; Андрейкив, Андрей Иванович; Andreykiv, Andrii I. (Одеса, 2018)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.11 – міжнародне право. – Національний університет «Одеська юридична академія». – Одеса, 2018. Дисертація присвячена дослідженню ролі міжнародних судових установ у процесі формування та реалізації норм звичаєвого міжнародного права. Висвітлено основні етапи становлення і розвитку доктрини та практики щодо звичаєвих норм у системі джерел міжнародного права, дано власне визначення звичая як джерела міжнародного права. Проаналізовано окремі елементи норми міжнародного звичаєвого права (практики та opinion juris) органами міжнародного судочинства, визначено часові, кількісні та функціонально-правові умови, необхідні та достатні для формування звичаєвих норм. Нормою звичаєвого міжнародного права визначено як юридично обов’язкове, позадоговірне правило поведінки, яке встановлюється його суб’єктами шляхом визнання юридично обов’язковою певну практику взаємних відносин. Суть реалізації норм звичаєвого міжнародного права судами міжнародної юрисдикції полягає у виконанні ними регуляторної, ціннісно-орієнтаційної та інших функцій. Запропоновано розглядати застосування конкретного міжнародноправового звичаю міжнародними судами як окрему (дискретну) процедуру, яка полягає: по-перше, у встановленні права, що регулює правовідносини, які є предметом спору; по-друге, у виявленні відповідності поведінки сторін спору нормі звичаєвого характеру через її окремі елементи – практику та opinio juris. Діяльність судових органів щодо звичаєвого нормотворення доцільно розглядати як квазіправотворчу. Досліджено практику застосування звичаєвих норм ЄСПЛ, який у своїй діяльності встановлює наявність міжнародного звичаю опосередковано, тобто посилається на факти, визначені рішеннями інших міжнародних установ, зокрема Комісії міжнародного права та МС ООН. Для підтвердження існування opinio juris як спільного визнання відповідної звичаєвої норми, ЄСПЛ досліджує практику держав із врахуванням їх національного законодавства. Зазначена процедура в теорії міжнародного права отримала назву «Європейський консенсус».

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.11 – международное право. – Национальный университет «Одесская юридическая академия». – Одесса, 2018. Диссертация посвящена исследованию роли международных судебных учреждений в процессе формирования и реализации норм международного обычного права. В работе освещены основные этапы становления и развития доктрины и практики в отношении обычных норм в системе источников международного права. Дано авторское определения международного обычая, исходя из особенности его правоприменения международными судебными учреждениями. Практика государств и признание его в качестве обязательной нормы раскрыты через специальные процедуры правоприменения судами собственной юрисдикции. Проанализировано отношение к отдельным элементам нормы обычного права, определенны условия, которые необходимы и достаточны для формирования обычных норм. Рассмотрено соотношение обычного правообразования и практики международных судов в отношении международного обычая, при этом установлены особенности реализации обычных норм в разрезе разных международных судебных учреждений. Раскрыты специфические черты толкования обычных норм этими учреждениями, в результате чего признается факт существования и сферы их действия. Установлена роль обычаев в практике Международного суда ООН, Международного уголовного суда, трибуналов ad hoc по Руанде и бывшей Югославии. Предложено рассматривать деятельность международных судебных учреждений в сфере международного обычного правотворчества как квазиправотворческую, а в правоприменении как комплементарную. Проанализирована практика применения обычных норм Европейским судом по правам человека и органами международного уголовного правосудия

Thesis for obtaining of a scientific degree of candidate of legal sciences under the specialty 12.00.11 – international law. – National University «Odesa Academy of Law». – Odesa, 2018. The thesis explores the role of international judicial bodies in the process of formation and realization of customary international law. Customary international law, being general practice accepted as law, is formed by the instances of conduct that are coupled with opinio juris. It was found that the official definition of custom as a source of international law has institutional nature and is contained in the provisions of the Statute of the International Court of Justice. Thus, the understanding of custom as the form of law and as a rule, which establishes the binding behavior of the subjects of international legal relations, can be possible though the activity of judicial bodies. It is worth mentioning, that according to general practice new states cannot arbitrarily choose legally binding rule of customary international law, as they have the responsibility to abide by the all customary rules, which were established before the creation of a state. Special attention is paid to the psychological element of international custom (opinion juris), which has a major role in cases of absence of repetitive practice in international relations on existence of a certain international custom. It is important to note that the party, which applies to international judicial body and substantiates its position by customary international law rules, has to provide credible evidence that this rule is of customary nature. International judicial bodies in turn assess legal positions provided, acknowledges the existence of customary rule elements needed and decides on its application. International judicial bodies cannot recognize customary nature of a rule by any other consideration. When the judicial body applies custom as generally binding rule, in addition to positive practice of the application of customary rules, a negative practice has a big importance as well – when a court refuses to apply customary rule or denies its customary nature. The practice of parties to a treaty (among themselves) is likely to be chiefly motivated by the conventional obligation, and thus is generally less helpful in ascertaining the existence or development of a rule of customary international law. Such practice is normally just that, sometimes serving as a means of interpretation of the treaty under the rules set forth in article 31 (3) (b) or article 32 of the Vienna Convention on the Law of Treaties. The legal effect of rules of customary international law mainly depends on consent of the state, which can be expressive or tacit. It was found that the application of customary international law rules in the procedure of the International Court of Justice is to be considered in several aspects. The Court decides on the basis of customary international law rule, parties to the dispute, however, use customary rules of international law for arguing and defending its positions. The European Court of Human Rights in its activities, referring to the practice of the International Court of Justice, can determine the existence of international custom not directly but indirectly – by relying on facts determined by other bodies, including the International Law Commission and the International Court of Justice. Such position seems appropriate since the ECHR, unlike the International Court of Justice, is precluded from determination of the existence of such rule. In addition, in some cases the ECHR examines the practice of certain states and takes into consideration their domestic laws in order to reaffirm the existence of opinion juris in the customary international law rule. This procedure received the name «European Consensus» in the theory of international law, and is being more widely used in the scientific circulation. Application of customary international law rules by the international criminal jurisdiction bodies has some peculiar aspects: most of the practice on the existence and application of customs was created by the ICTY. It was pointed out that other courts and tribunals limited themselves to refer to the ICTY’s practice; unlike practice of other judicial bodies, in the international criminal law opinion juris has the leading role, though it also uses two-elements concept; unlike the tribunals the Statute of the ICC accords much less prominent role to customary rules, which are applied in the cases of impossibility of the use of the Statute and other treaties.
дисертація на здобуття наукового ступеня кандидата юридичних наук
Андрейків А. І. Роль міжнародних судових установ у формуванні та реалізації звичаєвого міжнародного права : автореф. дис. ... канд. юрид.наук : 12.00.11 / А. І. Андрейків. - Одеса, 2018. - 22 с.
Keywords: норми звичаєвого міжнародного права; міжнародні судові органи; іманентна компетенція; двоелементна структура звичаєвої норми; міжнародно-правова доктрина; нормы обычного международного права; международные судебные органы; имманентная компетенция; двухэлементная структура обычной нормы; международно-правовая доктрина; customary international law rules; international judicial bodies; eminent competence; two-elements structure of customary rule; international legal doctrine